Injuries in netball - A systematic review - Downs, C.; Snodgrass, S. J.; Weerasekara, I.; Valkenborghs, S. R.; Callister, R. (Sports Medicine - Open, 2021)
Background Netball is estimated to be played by more than 20 million people worldwide, but there is evidence of high injury incidence. A thorough understanding of the types and rates of netball injuries is essential for effective injury management and prevention strategies to be developed and implemented. This systematic review summarises the published findings with respect to injury types, participant characteristics and any identified risk factors for netball injuries.